Knowledge Assessment of Hospital Staff Regarding Biomedical Waste Management in A Tertiary Care Hospital - Bathma , Vishal; Likhar , Swarn K; Mishra , Mahesh K; Athavale , Arvind V; Agarwal , Sanjay; Shukla , Uma S (National Journal of Community Medicine, 2012)
Background: Biomedical waste (BMW) is waste generated during diagnosis, treatment or immunization of human beings or animals. Approximately 10-25% of the Bio-Medical waste is hazardous and can be injurious to humans or animals and deleterious to environment. It is estimated that annually about 0.33 million tones of hospital waste are generated in India. Objectives: To assess the knowledge regarding hospital waste management amongst hospital staff. Material and Methods: The study comprises of assessment of the knowledge regarding BMW management. For this purpose, a 10% sample of each of the 4 categories of staff on roll was randomly selected for the study; the sample consisted of 110 respondents: 38 doctors, 44 nurses, 21 Lab- technicians and 7 waste handlers/supporting staff. Results: The knowledge of doctors about BMW management & handling rule was much better (92.1%) as compared to nurses (54.5%) and Lab-technicians (47.6%) and it was statistically significant (p-value < 0.05). Conclusion: The doctors where observed to be good in theoretical knowledge. While in case of nurses and lab-technicians the reverse was true. Recommendation: The need of comprehensive training programs regarding Bio-Medical waste management is highly recommended to all hospital staff.